Women Pioneers of Public Education - Herbst, J. author. aut Link
XI, 217 p. 7 illus.
Keywords: The book narrates the story of how the school, founded by women pioneers of public education in a Rocky Mountain mining settlement, became the centre and sustaining force of the town's community life from its beginning in the 1870s to the present day.